Health vulnerability and adaptation of community in the repetitive haze area: Phayao Province, Northern Thailand case study: 10.55131/jphd/2023/210311 - Sangkham, Sarawut; Sarndhong, Kritsada; Somjit, Pornpana; Ruxsanawet, Kingkarnonk; Kitchanapaibul, Siwarak (Journal of Public Health and Development, 2023)
This was a cross-sectional study to examine health vulnerability and adaptation of community in the repetitive smog area and transboundary haze effect: Phayao Province. According to the findings, the majority of people were male (61.86%), with a high-level of 35.70%, a low-risk level of 34.10%, and a medium risk level of 30.20%, in that order. According to the findings of this study, income was shown to be positively correlated with quality of life (r=0.136), body mass index (BMI) (r=0.116), risk level (r=0.213), adaptive capability (r=0.364), and vulnerability (r=0.364), all significant at p<0.05. Furthermore, multi-variable analysis to determine the predictive factors affecting groups with a tendency to be health vulnerable found that sensitivity affecting health vulnerability was adjusted OR: 7.61, B: 2.09 (S.E.: 0.03), Wald: 90.10 (p<0.01). To minimize vulnerability to the repeated haze area in the next decades, adaptation activities and a more conscious effect and sensitivity of the health sector are critically needed. The health vulnerability assessment of smog communities adaption suggestions were included in local public health risk planning and monitoring.